MODEL KEGIATAN KEPRAMUKAAN BERBASIS PARADIGMA INTEGRASI DI SD ISLAM QUR’ANI BANDA ACEH - Zikraul Husna; Muqowim Muqowim; Dibrina Raseuki Ginting; Veni Veronica Siregar; Rif'atul Fadilah (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2021)
Scouting activities are external activities that take advantage of teaching arrangements and adjustments for each scout section that has noble character. This research means directing and familiarizing every part of the scouts to have a sensible personality. Reconnaissance exercises are very successful in instilling character in the young children of the class. The reason for holding this exam is to decide on the technique of observing character values at SD Islam Al-Qur'an Banda Aceh. This examination uses an interesting subjective where data collection is completed by interviews, observation and documentation. The consequences of learning exercises that contain character appreciation and have a positive impact are directed through the level of consistency of adjustment. The framework between the training program and students is completed in a coordinated manner. So often reconnaissance drills are directed through constant adjustments.Keywords: Scouting Activities, Elementary School, Integration